OLIGO CHITOSAN TEST IN THE INITIAL BULBIL GROWTH OF ILES-ILES (Amorphophallus muelleri Blume) - Sumarwoto Sumarwoto; Sugeng Priyanto (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2020)
Oligo chitosan is a supplement that can increase growth, accelerate flowering, and increase productivity in several types of agricultural crops, rice and horticultural commodities. The findings of this study, encourage the authors, to further test the Oligo chitosan on the initial growth of the bulbs of Iles-iles. It is known, that Iles-iles (Amorphophallus muelleri Blume) or